2013
DOI: 10.1016/j.stem.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Myeloproliferative Neoplasia Remodels the Endosteal Bone Marrow Niche into a Self-Reinforcing Leukemic Niche

Abstract: SUMMARY Multipotent stromal cells (MSC) and their osteoblastic lineage cell (OBC) derivatives are part of the BM niche and contribute to hematopoietic stem cells (HSC) maintenance. Here, we show that myeloproliferative neoplasia (MPN) progressively remodels the endosteal BM niche into a self-reinforcing leukemic niche that impairs normal hematopoiesis, favors leukemic stem cell (LSC) function and contributes to BM fibrosis. We show that leukemic myeloid cells stimulate MSCs to overproduce functionally altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
582
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(622 citation statements)
references
References 39 publications
29
582
1
10
Order By: Relevance
“…Functional and gene expression studies using RNA sequencing recently demonstrated that Cxcl4 also induces migration of Gli1 + stromal cells and their myofibroblast transdifferentiation, thus mediating central cellular processes in BM fibrosis (Figure 2). Significant downregulation of the chemokine stromal‐cell derived factor (SDF)‐1 (Cxcl12) was also observed, in line with previous studies characterizing niche cells in MPN 17, 34. Interestingly, deletion of Cxcl12 in stromal cells was shown to increase the number of circulating platelets 34, 55, and studies in patients with MF have suggested that the BM microenvironment is deprived of active Cxcl12 56.…”
Section: Similarities To Solid Organ Fibrosis – Proinflammatory Cytoksupporting
confidence: 82%
“…Functional and gene expression studies using RNA sequencing recently demonstrated that Cxcl4 also induces migration of Gli1 + stromal cells and their myofibroblast transdifferentiation, thus mediating central cellular processes in BM fibrosis (Figure 2). Significant downregulation of the chemokine stromal‐cell derived factor (SDF)‐1 (Cxcl12) was also observed, in line with previous studies characterizing niche cells in MPN 17, 34. Interestingly, deletion of Cxcl12 in stromal cells was shown to increase the number of circulating platelets 34, 55, and studies in patients with MF have suggested that the BM microenvironment is deprived of active Cxcl12 56.…”
Section: Similarities To Solid Organ Fibrosis – Proinflammatory Cytoksupporting
confidence: 82%
“…Expanded OBCs are leukemia-trained, thereby effectively supporting leukemic stem cells (LSCs) but compromising the ability to maintain normal HSCs. Indeed, MPN development remodels an endosteal BM niche to form a self-reinforcing leukemic niche [35].…”
Section: Oncogenesis In Abnormal Nichesmentioning
confidence: 99%
“…In the same model, a suppression mechanism has been observed. Leukemic niche cells or MPN-expanded OBCs undergo compromised HSC-supportive activities that greatly downregulate numerous HSC retention factors [35].…”
Section: Dissemination Of Malignant Cells Affects Normal Hematopoiesismentioning
confidence: 99%
“…Existe-t-il alors une nouvelle niche spé-cialisée, la niche leucémique, permettant aux cellules souches BCR-ABL + de persister et de proliférer ? Les résultats des travaux exposés ci-dessus semblent montrer que le concept de niche leucémique est une réalité dont il faut désormais tenir compte dans les stratégies d'éradication de la LMC [22,25]. Le traitement par ITK entraîne chez une majorité de patients une rémission moléculaire.…”
Section: Concept De Niche Leucémiqueunclassified
“…Chez les patients atteints de LMC, plusieurs travaux ont suggéré que ce dialogue pouvait être altéré au profit des cellules leucémiques. Ainsi, en étudiant un modèle de souris transgénique exprimant de façon inductible l'oncogène BCR-ABL1, Schepers et al ont montré qu'une interaction directe entre les cellules leucémiques myéloïdes et les CSM était à l'origine d'un remodelage de la niche ostéoblas-tique [22]. Sous l'influence des cellules leucémiques et de facteurs solubles comme la TPO, les CSM seraient alors conduites à donner naissance à un nombre élevé de cellules ostéoblastiques anormales.…”
Section: Csh De Lmc Et Niche Hématopoïétique : Un Dialogue Modifiéunclassified